Transaksi Jual Beli Melalui Media Instagram Menurut Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Eletronik - I Made Satria Wibawa Tangkeban; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
The internet is an electronic and information medium that is developing very rapidly. The internet is widely used in various activities, namely trade, trading activities that use the internet known as e-commerce. Trading on the internet itself raises many problems related to the law and all its risks. Problems that can arise include default. The research aims are to analyze the rights and obligations of the parties in buying and selling transactions via Instagram and the legal consequences that arise if the seller in the sale and purchase transaction through Instagram defaults. The research method used is normative legal research, with using statutory approach. Primary sources of legal materials, sources of secondary legal materials were analyzed using systematic interpretation techniques. The result shows that in the buying and selling activities carried out on Instagram, there are often deviations in rights and obligations that are no longer in accordance with existing norms in society and legal remedies that can be taken if there is a default from one of the parties, be it the seller. and buyers who make online transactions can be sued within the environment of the general court or outside the court and can be subject to direct fines for parties who do not perform in default.